Statues of Buddha, Bodhisattvas, Taoist deities and Folk Gods - Mumbai Archive Project Team (Jio Institute, 2024)
Statues of Buddha, Bodhisattvas, Taoist deities, and folk gods are placed in the central shrine. Within the room, smaller shrines dedicated to specific deities or ancestors are present, each accompanied by its own set of offerings and decor. Candles are lit in front of the deities or on altars. Offerings, such as fruits, flowers, tea, and food, are arranged on altars as gifts to deities and ancestors. Worshippers light incense sticks as an offering to deities, to honour ancestors, and to purify the space.